Health Promoting Behavior in Pregnancy - Srisawad, Kanjana (Journal of Research in Nursing-Midwifery and Health Sciences, 2018)
The research objectives were to study the health promoting behavior in pregnancy, to compare their health promoting behavior in each quarter of trimester, and to do Confirmatory Factor Analysis (CFA) of them. There were 500 samples of primigravidarum, attending antenatal care at Sirindhorn Hospital who were selected by multi-stage random sampling. The research tools were demographic questionnaire and health promoting behavior in pregnancy measures. Data were analyzed by descriptive statistics, one way-ANOVA and Confirmation Factor Analysis. The research found that; 1) the average level of health promoting behavior in pregnancy overall was 3.82 2) their health promoting behavior in each quarter of trimester were no significant difference, and 3) their Confirmatory Factor Analysis showed chi-square=1.977, df=6, p-value= .922; the value of c2was no statistically different from zero, RMSEA= .000 and RMR= .002, which was closer to 0, GFI= .999, and CFI= .995, which closed to 1 and c2/ df=329, which less than 2, it meant this model was consistent with the empirical data.